Adat, Islam, and Dakwah Movement in Bayan, North Lombok - Budiwanti, Erni (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
Of the three millions Lombok population the Bayanese cover around 5,000 people, who have embedded Islam since 16th century ago. Despite their adherence to Islam, they still bold very strongly the adat (custom) to worship divine ancestors and various guardian spirits. This bas instigated dakwah (missionary) movement led by Tuan Guru (teacher) and his loyal disciples to purify Islamic ritual that violates the tauhÄ«d (monotheism), They act as the agents of change who want to transform the Bayanese syncretic belief. The mission has put the Bayanese in dilemma. On one hand, it is very sensitive because it attempts to alter the sacred ancestral values which are highly respected. On the other hand, this mission offers free education and ecological project which intends to increase the living standard of local Bayanese